Polarization‐Assisted Visual Secret Sharing Encryption in Metasurface Hologram - Zhenfei Li (Wiley-VCH, 2021)
Secret sharing is an advanced encryption method that distributes the secret information into multiple participants and only the predesigned subsets of authorized participants can recover the secret by gathering their independent subinformation. Herein, the security level of secret sharing using electromagnetic manners is further expanded and a simple platform for the realization and direct observation of secret sharing encryption using metasurface hologram is presented. As a proof of concept, a polarization‐assisted secret sharing phase encoding method by integrating visual secret sharing scheme with phase encoding technology using orthogonally polarization‐multiplexing metasurface is experimentally presented. The method achieves its encryption security and decryption simplicity by hiding the secret information into a pair of orthogonal polarization channels ensuring that the secret information is direct decryption as the two channels participate simultaneously while fully concealed in single channel. This scheme may pave a new route for future information encryption, hiding, and authentication.